The Effect of Workload, Role Conflict, and Work Environment on Cyberloafing Behavior in the Marine and Fishery Services of The Riau Islands - Asmaul Husna; Nurhasanah Nurhasanah; Teddy Prayoga (Journal of Research in Business, Economics, and Education, 2022)
This study aims to explain the effect of workload, work conflict and work environment on cyberloafing behavior. The population in this study were 32 employees at the Department of Maritime Affairs and Fisheries of the Riau Islands Province. Sampling with the saturated technique, the number of samples as many as 32 employees. This type of research is quantitative research. In the questionnaire, validity and reliability tests were carried out. Data were analyzed using multiple linear regression analysis, including t test, f test and coefficient of determination. The results showed that partially the workload (X1), work conflict (X2) and work environment (X3) variables had a significant effect on cyberloafing. The results of the F test obtained that the calculated F value is 12,455 with an F table value of 2.95 identifying that the workload, work conflict and work environment variables simultaneously have a significant effect on the Cyberloafing variable (Y). Based on the results of the coefficient of determination test. About 53% of cyberloafing variables are influenced by workload, role conflict and work environment variables. The remaining 47% is influenced by other factors not explained in this study.